Incremento del net promoter score a través de la gestión por procesos: estudio de caso en el retail de uniformes médicos - Ibañez Rodriguez, Gustavo Armando (2024)
This study aims to enhance customer satisfaction in the medical uniforms sector through the implementation of process management, focusing on the Net Promoter Score (NPS). Over eight months, the Plan-Do-Check-Act (PDCA) method was applied, assessing its impact through surveys on a sample of 378 customers. The mixed-methodological approach integrates quantitative and qualitative data to evaluate the influence of process management on customer satisfaction. Results, supported by statistical analysis, underscore the imperative need for effective process management to drive continuous improvement in customer satisfaction, especially in the dynamic retail environment. This study bridges the gap in correlation between process management and tangible improvements in NPS within the retail context, emphasizing its relevance in a post-pandemic scenario where customer expectations and competition demand optimized business practices.